IMPLEMENTASI ALGORITMA ADVANCED ENCRYPTION STANDARD DAN TRIPLE DATA ENCRYPTION STANDARD UNTUK MENGAMANKAN CITRA DIGITAL - Winafil, Mahadi; Sinurat, Sinar; Zebua, Taronisokhi (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Digital images that are personal and confidential are very vulnerable to wiretapping by irresponsible parties. Especially if distributed via the internet network such as on Facebook, WhatsApp and e-mail chat based applications. Images that are sent sometimes are often confidential images and must be maintained. In order to maintain the security of digital images can be done by utilizing cryptographic techniques. Cryptographic techniques can secure digital images by changing pixel values from digital images so as to produce different pixel values from the original image to be secured. This research will use AES 128 bit and Triple DES methods for encryption and decryption of digital images on client-server based applications. The results of the encryption AES algorithm will be re-encrypted with the Triple DES Algorithm so as to produce pixel values that are far different from the original pixel values. Keywords: cryptography, image, AES, Triple DES